More answers

-10 + (-6) = -10 - 6 = -16

Q: Evaluate the expression -10 plus (-6)?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6(a+b)

'X-7 plus 23-6' can be simplified and expressed as: 'x+10'

By multiplying out the brackets it then is -10+24t-48 = 24t-58 when simplified

Yes, -6+x is the same as x-6.

6 is the coefficient of n in this expression.

Related questions

12 - 10 + 4 = 6

46

16

33

X = 6 5x + 2x = 42

You cannot solve it though it is possible to evaluate the expression. -5 + 9 * 6 = -5 + 54 = 49

6(a+b)

14

'X-7 plus 23-6' can be simplified and expressed as: 'x+10'

Yes.

55

15z = 15 x 6 = 90